Wetting of Single Crystalline and Amorphous Silicon Surfaces: Effective Range of Intermolecular Forces for Wetting - Özçelik, Hüseyin Gökberk; Barışık, Murat; Özdemir, Abdullah Cihan; Kim, Bohung; Barışık, Murat (Taylor and Francis Ltd., 2020)
Wetting at nanoscale is a property of a three-dimensional region with a finite length into the solid domain from the surface. Understanding the extent of the solid region effective on wetting is important for recent coating applications as well as for both crystalline and amorphous solids of different atomic ordering. For such a case, we studied the wetting behaviour of silicon surfaces at various crystalline and amorphous states. Molecular distributions of amorphous systems were varied by changing the amorphisation conditions of silicon. Semi-cylindrical water droplets were formed on the surfaces to be large enough to remain independent of line tension and Tolman length effects. Contact angles showed up to 38% variation by the change in the atomic orientation of silicon. Instead of a homogeneous solid density definition, we calculated different solid densities for a given surface measured inside different extents from the interface. We correlated the observed wetting variation with each of these different solid densities to determine which extent governs the wetting variation. We observed that the variation of solid density measured inside a 0.13 nm extent from the surface reflected the variation of wetting angle better for both single crystalline and amorphous silicon surfaces.
Keywords: Surface wetting; Crystalline materials; Molecular dynamics